Avaliação da eficiência de biofertilizante à base de aminoácidos na cultura do trigo - Leiser, Alan Willy (2024)
The use of bioinputs has proven to be an ecological and effective option for agricultural management, minimizing environmental impacts and risks to human health. For Brazil, a major exporter of agricultural products, the adoption of bioinputs, such as amino acids, could be highly advantageous. Therefore, this study aimed to evaluate the efficiency of a foliar-applied biofertilizer in wheat cultivation (Triticum aestivum L.). The foliar fertilizer used was an amino acidbased product derived from bovine collagen. The treatments evaluated consisted of two doses of the amino acid-based product applied via foliar spray (1 and 1.5 L ha-1) at three phenological stages of crop development (stem elongation, flowering + stem elongation, and flowering) and a control (without application). The experimental design was a randomized block design with four replications. The spraying was carried out using a CO2 backpack sprayer. The plots consisted of 11 rows of 8 m, with a spacing of 0.17 m between them, totaling 15 m². At harvest, 1 m from each end of the rows and two rows from each side of the plots were discarded. The parameters evaluated included grain yield, hectoliter weight, protein content, and thousand-grain weight. In the greenhouse, following these evaluations, the grains were subjected to an emergence test, and 15 days after this assessment, the seedling height, root length, and shoot dry matter production were evaluated. The data were subjected to analysis of variance, and the means were compared using Tukey's test at a 5 % significance level. The amino acid-based biofertilizer applied via foliar spray to wheat, at doses of 1 or 1.5 L ha-1, during stem elongation, heading, or both stages, did not result in increased grain yield or post-harvest quality in this crop.